2018
DOI: 10.1111/eufm.12196
|View full text |Cite
|
Sign up to set email alerts
|

Employee treatment and its implications for bondholders

Abstract: We examine the various channels through which the quality of a firm's employee relations can affect the welfare of bondholders. Our evidence suggests that better employee treatment benefits bondholders and leads to a lower bond spread by enhancing a firm's productivity, and by reducing the likelihood of product failures, labor strife, and employee turnover. However, a higher level of satisfaction is costlier for bondholders in firms facing more severe financial constraints or agency problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…In the first-stage regression model, this study employs the average CSR performance variables of a firm's neighboring ones (Geo_CSR, neighboring firms in the same three-digit ZIP area in a given year) 5 as the instrument variables of the firm's CSR performance variables. Jiraporn et al (2014) and Chen et al (2018) also show that Geo_CSR variables satisfy the criteria of good instrument variables, namely, the relevance condition and the exclusion condition.…”
Section: V2 Endogeneity Issue Of the Relation Between Csr Performance And Annual Report Readabilitymentioning
confidence: 89%
“…In the first-stage regression model, this study employs the average CSR performance variables of a firm's neighboring ones (Geo_CSR, neighboring firms in the same three-digit ZIP area in a given year) 5 as the instrument variables of the firm's CSR performance variables. Jiraporn et al (2014) and Chen et al (2018) also show that Geo_CSR variables satisfy the criteria of good instrument variables, namely, the relevance condition and the exclusion condition.…”
Section: V2 Endogeneity Issue Of the Relation Between Csr Performance And Annual Report Readabilitymentioning
confidence: 89%
“…In a similar vein, Mao and Weathers (2019) use a slightly different employee treatment measure to show a significant positive association between favorable employee treatment and firm innovation performance. Chen et al. (2019) document evidence to suggest that treating employee better may have favorable benefits to bondholders because such companies show a lower bond spread.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In a similar vein, Mao and Weathers (2019) use a slightly different employee treatment measure to show a significant positive association between favorable employee treatment and firm innovation performance. Chen et al (2019) document evidence to suggest that treating employee better may have favorable benefits to bondholders because such companies show a lower bond spread. Zhang et al (2020) find a significant negative association between employee treatment and the likelihood of corporate fraud, which suggests that such firms are more likely to honor labor contracts and value long-term relationships with their employees.…”
Section: Employee Treatmentmentioning
confidence: 99%
“…Many scholars and practitioners have suggested that a supportive workforce environment not only helps firms keep talented employees (Hom et al 2017;Kundu and Lata 2017), but also motivates employees to be more cooperative and efficient (Bloom et al 2011). Firms with a supportive workforce environment have high performance and valuation levels (Chen et al 2019;Habib et al 2021) and are more innovative compared to firms with a non-supportive workforce environment (Edmans 2011). Impliedly, a supportive workforce environment could be interpreted as a signal of higher levels of organizational effectiveness including employee engagement, commitment, and efficiency.…”
Section: Introductionmentioning
confidence: 99%